A study on maintenance management of primary school in case study (Kedah & Selangor) / Siti Aisyah Che Ad @ Saad - Che Ad @ Saad, Siti Aisyah (Faculty of Architecture, Planning and Surveying, 2013)
Maintenance is a continuous protective care of the fabric, contents and setting of a place. A maintenance plan is the most cost-effective way to ensure the ongoing value of any asset, particularly a registered place. The plan should include regular inspections, prompt attention to repairs and a cleaning program. Realizing the importance of maintenance in Malaysia, this dissertation which tittle “A Study On Maintenance Management Of Primary School In Case Study (Kedah & Selangor)” is documented.This research comprises of 6 chapters. This research intends to identify how the maintenance management was carried out at Primary School in Kedah and Selangor. Case study on two primary schools are located at Kuala Nerang, Kedah which is Sekolah Kebangsaan Tunku Abdul Rahman Putra and at Shah Alam, Selangor is Sekolah Kebangsaan Seksyen 9.Analysis for this research comprise of comparative and descriptive approach as well as statistical analysis which are based on case studies and questionnaire survey. Since the finding from the questionnaire and interview with the related person, it determined that both of primary school, the maintenance management was carried out by Pejabat Pelajaran Daerah (PPD).